Global burden of diabetes mellitus 1990–2021: epidemiological trends, geospatial disparities, and risk factor dynamics - Ciming Pan; Beiling Cao; Hui Fang; Yelu Liu; Shuhan Zhang; Wei Luo; Yuanjie Wu (Frontiers in Endocrinology, 2025)
Diabetes mellitus(DM) remains a significant global health challenge, characterized by high incidence and Disability-adjusted life years (DALYs) rates. A comprehensive understanding of the disease burden of DM is crucial for developing effective prevention and treatment strategies. This study analyzes the global burden of diabetes mellitus (DM) from 1990 to 2021 using data from the Global Burden of Disease Study. In 2021, DM caused 1.66 million deaths, with age-standardized mortality rising by 7.95% since 1990. While Type 1 diabetes (T1DM) mortality declined by 29.24%, Type 2 diabetes (T2DM) accounted for 97.1% of deaths, with a 9.75% mortality increase. Geospatial analysis revealed extreme disparities: Pacific Island nations exhibited incidence rates >800/100,000, contrasting with <3/100,000 in Costa Rica and China. T1DM burden predominated in high-latitude regions (e.g., Finland), whereas T2DM mirrored overall DM distribution. DALYs for T2DM surged by 42.32%, disproportionately affecting Low-SDI regions. Age-stratified analyses identified distinct patterns: T2DM incidence peaked at 59–69 years, while T1DM DALYs peaked in early-middle adulthood (40–44 years). Risk factor hierarchies highlighted metabolic risks (e.g., high BMI) for T2DM and ambient temperature effects for T1DM. Despite progress in T1DM management, rising T2DM burden underscores urgent need for targeted prevention strategies addressing obesity, dietary risks, and environmental determinants. Study limitations include potential GBD data inaccuracies and ecological design constraints. These findings emphasize the imperative for region-specific interventions to mitigate the evolving diabetes pandemic.